Design of a Low-Cost Autonomous Multitasking Robot for Educational and Competitive Applications - Borges, Lucas Gabriel Soares; Costa, Eduardo Casimiro; Guimarães, Davi Faria de Sousa; Maia, Eduardo Habib Bechelane; Araujo, Thabatta M. A. de; Cruz, Diego Fernandes da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This article presents a low-cost, autonomous multitasking robot designed and implemented by students of a High School technical. Multitasking robots are advantageous in critical environments, such as automated industries and extreme conditions, as they are equipped with features such as line following, object manipulation, obstacle avoidance, and distance measurement, among others. However, the complexity of these functionalities often leads to high production costs and the use of materials that are difficult to obtain. To address this challenge, we propose the design and implementation of a multitasking robot that is both accessible and sustainable. Its construction combined electronic components with disposable materials, enhanced through modeling and 3D printing techniques. The total robots' initial cost was reduced from R$438.94 to R$328.89. Testing has yielded promising results, as demonstrated by the robot's successful performance in the Regional Brazil Robotics Tournament. The main contributions include the creation of an affordable and functional multitasking robot that can be adapted for educational purposes and various socially relevant applications, promoting access and innovation in educational approaches to robotics.